Traditional chants in the life cycle of the Ilocanos - Aurelio, Mary Lou F. (2006)
The research ?Documentation of Iloko Traditional Chants in the Life Cycle? is envisioned as a tool in the search for Ilocano identity. This documentary research was conducted not only to revive a dying Ilocano tradition but also to identify and define Ilocano culture, specifically Iloko folk music, with the ultimate goal of transmitting this unique culture to succeeding generations. The Iloko folk songs that are documented in this research were carefully selected to depict the celebrated events in the life cycle of the Ilocanos, such as birth, love, courtship and marriage, and death. These are classified as duwayya (lullaby), dallot (courtship, betrothal, wedding and presenting the mat, and dung-aw (lamentation). This research project on Iloko music is envisioned as a permanent task for the nation, involving the collection, documentation, and research of data on traditional music, including performing them and transmitting and publishing folk music as scholarly endeavors.
Includes bibliographical references (pages 38-39).